Perancangan Sistem Informasi Absensi Menggunakan Metode QR Code Berbasis Android - Fitri, Andini Hadaina; Adiwisastra, Miftah Farid (Infotek: Jurnal Informatika dan Teknologi, 2024)
Attendance in the world of work is something that cannot be missed, because it is one of the performance assessments of an employee in the company as well as one of the indicators of determining performance every month. Therefore it is very important to record employee attendance correctly. CV Adi Bakti is one of the companies that still uses paper to record attendance. This causes employees to do things that are not expected, such as signing the wrong column or signing attendance for coworkers who are not present that day. In addition, attendance that is only in the form of sheets allows damage and loss and causes undocumented employee attendance reports every month. Seeing from this problem, the author designed an Android-based Attendance Information System using QR Code technology in order to provide convenience for companies in the attendance process and attendance reporting. This data collection uses observation, interview, and literature study methods. The system development method in this study uses the Prototype method. The results of this study are an Android-based Attendance Information System using QR Code technology that can assist companies in presenting employee attendance data accurately and quickly. Can make it easier for companies to make or recap employee attendance reports which are automatically printed on the system